Dynamic alteration in SULmax predicts early pathological tumor response and short-term prognosis in non-small cell lung cancer treated with neoadjuvant immunochemotherapy - Sun, Taotao; Huang, Shujie; Jiang, Yongluo; Yuan, Hui; Wu, Junhan; Liu, Chao; Zhang, Xiaochun; Tang, Yong; Ben, Xiaosong; Tang, Jiming; Zhou, Haiyu; Zhang, Dongkun; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Introduction We aimed to assess the effectiveness of the immune PET Response Criteria in Solid Tumors via SULmax (iPERCIST-max) in predicting tumor response to neoadjuvant immunochemotherapy and short-term survival in locally advanced NSCLC. Methods In this prospective cohort study, we calculated SULmax, SULpeak, metabolic tumor volume (MTV), total lesion glycolysis (TLG) and their dynamic percentage changes in a training cohort. We then investigated the correlation between alterations in these parameters and pathological tumor responses. Subsequently, iPERCIST-max defined by the proportional changes in the SULmax response (△SULmax%) was constructed and internally validated using a time-dependent receiver operating characteristic (ROC) curve and the area under the curve (AUC) value. A prospective cohort from the Sun Yat-Sen University Cancer Center (SYSUCC) was also included for external validation. The relationship between the iPERCIST-max responsiveness and event-free survival in the training cohort was also investigated. Results Fifty-five patients with NSCLC were included in this study from May 2019 to December 2021. Significant alterations in post-treatment SULmax (p<0.001), SULpeak (p<0.001), SULmean (p<0.001), MTV (p<0.001), TLG (p<0.001), and tumor size (p<0.001) were observed compared to baseline values. Significant differences in SULpeak, SULmax, and SULmean between major pathological response (mPR) and non-mPR statuses were observed. The optimal cutoff values of the SULmax response rate were -70.0% and -88.0% using the X-tile software. The univariate and multivariate binary logistic regression showed that iPERCIST-max is the only significant key predictor for mPR status (OR = 84.0, 95% confidence interval [CI]: 7.84 – 900.12, p<0.001). The AUC value for iPERCIST-max was 0.899 (95% CI: 0.784 – 1.000, p<0.001). Further, external validation showed that the AUC value for iPERCIST-max in the SYSUCC cohort was 0.889 (95% CI: 0.698 – 1.000, P = 0.05). Significantly better event-free survival (EFS) in iPERCIST-max responsive disease (31.5 months, 95% CI 27.9 – 35.1) than that in iPERCIST-max unresponsive disease (22.2 months, 95% CI: 17.3 – 27.1 months, p = 0.024) was observed. Conclusion iPERCSIT-max could better predict both early pathological tumor response and short-term prognosis of NSCLC treated with neoadjuvant immunochemotherapy than commonly used criteria.